Introducing Solid Foods - Linda B. Bobroff (EDIS)
Revised! FCS8546, a 5-page fact sheet by Linda B. Bobroff, will help parents know when and how to start feeding solid foods and how to help their infant make the change to table food as he or she grows into the toddler years. This revision includes updated feeding recommendations throughout and adds a section on food allergies. Includes information on finding reliable local sources for more information and recommended resources. Published by the UF Department of Family Youth and Community Sciences, April 2006.